Deep geoelectric structure in the Rohtak region using the magnetotelluric studies - Gupta, Gautam; Rao, C.K.; Gokarn, S. G. (My University, 1997)
Magnetotelluric studies conducted in the seismically active regions around Rohtak over two linear profiles showed a predominantly two dimensional behaviour with major and minor rotation directions along the E-W and N-S respectively, indicative of strong influence of an approximately N-S aligned 'conductive feature. The geoelectric structure indicates a 25 m thick surface layer with a resistivity of .1.4 ohm-m corresponding to the alluvium. The thickness of the second (30 ohm-m) and third (1.2 ohm-m) layers were 50m and 150m respectively. These are interpreted to be due to the Siwalik sedi¬ments below alluvium. The fourth layer is 3000-4500m thick and has a resistivity of 100 ohm-m. This is presumably the metamorphosed basement and is separated from the granitic basement by 500- 1500m thick highly conductive (1 ohm-m) layer, which presumably is the unconformity between the metamorphosed and granitic basements. A N-S oriented vertical conductive zone was delineated extending from near surface to depths of atleast 18 km. This conductive body is about 5 km wide (along E-W) and has a resistivity of I ohm-m. The vertical conductor is indicative of a N-S aligned active fault or fracture zone transverse to the strike of the Himalayan collision belt. The epicentral distribution of the earthquakes indicates that this fault may be of significance in understanding the seismicity of this region.
Keywords: Geophysics; Himalaya; Magnetotelluric studies; Indo-gangetic foredeep; Iohtak region